2018
DOI: 10.1177/1541931218621064
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches to Collecting Family Health History – A Preliminary Study Investigating the Efficacy of Conversational Systems to Collect Family Health History

Abstract: Knowing and compiling your family health information is an important, cost-effective and efficient way to help your doctor screen and monitor for risks of genomic diseases such as cancer. There are several ways to collect family health history, including the use of digital records. Digital records can be helpful for sharing and updating information among family members. However, minimal research has been conducted to compare the different data collection interfaces. This study focuses on evaluating the user’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This increased mental demand impacted performance and efficiency as seen from the increased task completion time and number of errors. 67,68…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This increased mental demand impacted performance and efficiency as seen from the increased task completion time and number of errors. 67,68…”
Section: Discussionmentioning
confidence: 99%
“…As confirmed by the qualitative feedback, participants felt the standard interface to be too wordy, thus impacting their cognitive load and supporting their preference for VCA interface. 64,66,70 Guidelines proposed by Stewart and Travis (2002) 68 suggest that effective interfaces are designed by considering the capacity limitation of the users and reducing the short-term memory load. The increase in the cognitive load may affect the user’s satisfaction while completing different tasks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VICKY 1.0 was shown to have good acceptability and feasibility among English speaking patients at a safety-net hospital [18]. Others have similarly shown that conversational systems are more usable compared to traditional interfaces for compiling family health histories [19]. Currently, VICKY 2.0 is undergoing a randomized controlled trial to determine its accuracy in collecting health history information compared to another publicly available digital tool (My Family Health Portrait, https://phgkb.cdc.gov/FHH).…”
Section: Introductionmentioning
confidence: 99%